Tackling Medical Deserts : Unearthing Factors that Influence Medical Students' Attitudes and the Path Forward - Marcec, Robert; Seils, Laura Alexandra; González, Ana Isabel; Dubas-Jakóbczyk, Katarzyna; Domagała, Alicja; Dan, Sorin; Flinterman, Linda; Likic, Robert; Batenburg, Ronald (Oxford University Press, 2023)
“Medical deserts,” areas characterized by limited access to healthcare services, are a growing global concern. These areas often face a shortage of healthcare professionals, which significantly contributes to poor healthcare access, reduced health outcomes, and health inequalities [1]. As future healthcare providers, medical students have the potential to address this issue by considering work opportunities in these underserved regions. However, despite various policy interventions in the European Union (EU), there remains a need to understand which measures are most effective in motivating, recruiting, and retaining (young) healthcare workers in medical desert areas. In Croatia, as in most other EU countries, medical deserts have emerged by regional disparities in age structures, economic resources, travel time to healthcare facilities, and healthcare provider ratios. These disparities often exist between urban and rural areas, with rural regions typically facing a higher degree of healthcare provider shortage. Addressing these disparities is essential to achieve equitable healthcare access for all populations, especially for those residing in remote and underserved regions. Studies have shown that medical students’ attitudes towards working in medical deserts are influenced by various factors, such as personal characteristics, socioeconomic status, education, and training [2–4].
Keywords: fi=Julkisjohtaminen|en=Public Management|